SUSTAINABLE FINANCE AND SOCIETY grand challenges of the new millennium. (ROUTLEDGE, 2025)
Sustainable Finance and Society explores how finance can be managed to address pressing global challenges.Part of the Routledge Business and Society series, this book investigates the evolving financial ecosystem shaped by new stakeholder capitalism. It examines how finance can be leveraged to benefit society while balancing environmental, social, and financial performance. Through a combination of theoretical insights and empirical studies, the book offers a comprehensive framework for understanding sustainable finance as a driver of societal well-being. This book provides a thorough analysis of sustainable finance, from the roles of financial markets and institutions to the rise of socially responsible investments. Key topics include sustainable investing evaluation, green finance, entrepreneurship, innovation, and the role of women in finance leadership. The book features a deep dive into the challenges and opportunities of managing finance for societal benefit, offering valuable insights for aligning financial practices with ethical, environmental, and social goals.It is essential reading for academics, researchers, and policymakers interested in finance for society. It is also relevant for finance practitioners, sustainability experts, and institutional investors looking to implement socially responsible financial practices and address the grand challenges of the 21st century.
Keywords: Finance -- Social aspects.; Social change -- Economic aspects.; elektronické knihy; electronic books